Persepsi Peserta Didik terhadap Penggunaan E-Learning Madrasah dengan Pendekatan Technology Acceptance Model (TAM) - Siti Nurjanah; Suprih Widodo; Dian Permata Sari (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
The challenge for an educator in keeping up with the times is that they must be able to provide and utilize ICT (Information and Communication Technology) which is expected to be able to direct and guide students to understand it. ICT-based learning processes or those involving technology are usually called E-Learning or Electronic Learning. One example is E-Learning Madrasah which is an application produced and issued by the Ministry of Religion. This research aims to analyze the perceptions of students using the Technology Acceptance Model (TAM) towards Madrasah E-Learning. The research method used is a quantitative approach by carrying out statistical-based testing on the data that has been collected. Researchers want to know students' perceptions of the acceptance and use of information technology in the form of Madrasah E-Learning. The research results prove that there is an influence between perception and use or acceptance of Madrasah E-Learning. It is known that for students, the variables Perceived Ease of Use and Perceived Usefulness have a positive effect on Acceptance of IT and have a dominant influence on acceptance of the E-Learning system.